Antiradical and Cytotoxic Activities of Varying Polarity Extracts of the Aerial Part of Euphorbia hirta L. - Perumal, Shanmugapriya; Mahmud, Roziahanim; Pillai Piaru, Suthagar; Wei, Cai Lee; Ramanathan, Surash (Hindawi Publishing Corporation, 2013)
Euphorbia hirta is a well-known ethnomedicinal plant with diverse biological activities.The aim of the present study is to investigate the antiradical activities of various solvent extracts of the aerial part of E. hirta as well as to determine the possible cytotoxicity of these extracts. The aerial part of E. hirta was extracted with different solvent systems in order to increase polarity. The solvents used were hexane, dichloromethane (DCM), ethyl acetate (EA), ethanol (EtOH), and methanol (MeOH). The contents of total phenols and total flavonoids were analyzed byUVspectrophotometry, whereas the potential free radical-scavenging activities of the extracts were evaluated using the stable free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH), the